A Comparison of Stool Enteropathogen Detection by Semiquantitative PCR in Adults With Acute Travelers' Diarrhea Before and 3 Weeks After Successful Antibiotic Treatment. (26th April 2019) - Tisdale, Michele D; Tribble, David R; Telu, Kalyani; Fraser, Jamie A; Connor, Patrick; Philip, Cliff; Odundo, Elizabeth; Reyes, Faviola; Simons, Mark P; Swierczewski, Brett; Lizewski, Stephen; Liu, Jie; et al.
Abstract: We evaluated stool enteropathogen detection by semiquantitative polymerase chain reaction (PCR) in 108 subjects with travelers' diarrhea before and 3 weeks after treatment. Stool samples from 21 subjects were positive for the same pathogen species at both visits. We discuss factors that should be considered when interpreting stool PCR data after treatment.